El índice de Coherencia de Políticas para el Desarrollo: midiendo la Agenda 2030 desde la Coherencia de Políticas para el Desarrollo - Martínez-Osés, P. J.; Gil-Payno, M. L. (Revista Iberoamericana de Estudios de Desarrollo)
The article presents the Policy Coherence for Development Index (PCDI) which is, as a whole, a new framework for understanding and interpreting the challenges of the Agenda 2030 and the public policies its approach requires. It provides also an ambitious monitoring system to assess countries’ compliance with the agreed commitments from the policy coherence for development perspective. Previously, the article exposes how the 2030 Agenda requires a new conceptual and instrumental framework in order to consolidate a new narrative about the development challenges based on the universality, integrality and multidimensionality, including also the global interdependencies and interconnections that characterize today’s world. This framework must also provide a solid measurement of progress and setbacks regarding the Sustainable Development Goals and targets internationally agreed.